Tie Content in Professional Networks - Olga Zarzecka (Copenhagen Business School (CBS), 2016)
Professional networks of senior managers have indisputable value for them as well as for their organizations. In recent years, much attention has been given to the structure of these networks as it reflects senior managers' opportunity to access valuable resources. Surprisingly, the actual resources that senior managers acquire through their network ties, i.e. the tie content, remain heavily understudied. Hence, the purpose of this dissertation is to answer the following question: What resources flow through informal ties in senior managers' professional networks, and why? The first chapter introduces the topic of this dissertation as well as the overall research question. The three next chapters are empirical studies of informal ties in professional networks of Danish senior managers, that together attempt to answer the overall research question. Chapter 2 looks into gender differences in resource exchanges and the effect of these differences on the number of, and extent to which, resources are provided by a network tie. Chapter 3 explores how firm underperfomance and social identity with corporate elite alter types of resources a network tie provides. Chapter 4 focuses on a tie's internal dynamics and studies the effect of friendship on the extent and novelty of professional advice a tie provides. The fifth and final chapter of this dissertation summarizes the findings of the research papers in the light of the overall research question. Essentially, this dissertation suggests that the strategic value of professional informal network ties is contingent on the actual combination of resources these ties provide. Furthermore, this combination depends on micro-level mechanisms that affect three dimensions of tie content: the number of resources, the type of resources and the extent to which these resources are provided by informal network ties.
hdl:10398/9357
Keywords: 650